Pensão por morte no Regime Geral da Previdência Social - Barros, Vera Regina Cotrim de (2008)
This research consists of a systemic approach of the benefits of the death pension in the General Social Security Regime, in the present Brazilian Social Security system. Starting from a historic context, labor, based on a legislation research, doctrine and jurisprudence, reveals the laws treatment regarding this matter and evokes relevant problems, some just emerged, related to new social needs, that were analyzed and instantiated; and the conclusion reached related to the comprehension and application of the constitutional norm and infra-constitutional that regulate our country s Social Security